Joseph and Aseneth after Antiquity a study in manuscript transmission - Wright, Jonathon Stuart; Joseph et Aseneth; Walter de Gruyter GmbH & Co. KG (Berlin Boston De Gruyter, 2025)
"Joseph and Aseneth expands a few verses from the book of Genesis into a novella-length work. It is increasingly used as a source for Judaism and Christianity at the turn of the Common Era. Scholarly attention has largely focused the work's provenance, the priority of a longer or shorter text version, and the implications for interpretation. But few have engaged with the work's manuscript witness and transmission. This study returns to the sources. It considers how the redaction and translation of Joseph and Aseneth affected its interpretation, and looks at the interests of the redactors and copyists. Its findings warn against placing too much weight on details that lack such an importance in the manuscript tradition. Important contributions made in this monograph include: a detailed study of the two earliest versions, the Syriac and Armenian translations; focus on the Greek manuscripts of the three longest families (f, Mc, a); analysis of four abridged versions (family d, E, Latin 1 and so-called "early modern Greek"); the first available synoptic edition of the Greek versions of the story, including the first edition of manuscript E." -- Provided by publisher
Textausgabe griechisch in griechischer Schrift, Erläuterungen english
Keywords: Joseph and Aseneth -- Criticism, interpretation, etc -- History; Joseph and Aseneth -- Translating -- History; Joseph and Aseneth -- Versions; Joseph and Aseneth -- Criticism, Redaction